Determinants of transfer pricing aggressiveness and the mediation role of tax burdens: Evidence from Indonesia - Febriyadi Tri Hadmoko; Ferry Irawan (University of Islam Malang, 2022)
Transfer pricing aggressiveness is influenced by various factors, including the complexity of operations, foreign direct investment, and tax haven utilization. This study was conducted to re-examine the factors that affect the transfer pricing aggressiveness by including the tax burden as a mediating variable which is expected to explain the inconsistency of the results of previous studies. This study uses data from manufacturing companies listed on the Indonesian Stock Exchange from 2016 to 2020 with a total observation of 350. The analysis technique uses panel data regression with Fixed Effect Model and Random Effect Model approaches. The results of the study show that the complexity of operations and tax haven utilization has a positive effect on transfer pricing aggressiveness. However, foreign direct investment does not affect transfer pricing aggressiveness. Further analyses indicate the tax variable partially mediates the effect of complexity operation and tax haven utilization on transfer pricing aggressiveness. In addition, the tax variable only has an indirect effect of foreign direct investment on transfer pricing aggressiveness. This means that foreign direct investment is used as a vehicle for transfer pricing.